Stability of finger millet (Eleusine coracana L.) yield using additive main effects and multiplicative interaction analysis (International Journal of Agricultural Research, Innovation and Technology, 2023)
In Ethiopia's mid and lowlands, where rainfall is erratic, finger millet (Eleusine coracana L.) is an important cereal crop. Finger millet yield is low partly due to variety instability and low yield potential. Field experiments were conducted in Boricha, Dore Bafano and Halaba districts of Southern region, Ethiopia, in 2018 and 2019, during the main cropping season from early May to October, to identify finger millet genotypes with high yield and wide adaptation. Eleven finger millet genotypes (ten improved and one local check) were grown in a randomized complete block design with four replications. AMMI analysis generated four principal components (PCs) with PC1 and PC2 being statistically significant (p